Telaah Pemikiran Ilmu Pengetahuan Thomas Samuel Kuhn dan Implikasinya Pada Pemikiran Islam - Aprina, Eka Anisa (Pendidikan Islam Pascasarjana IAIN Jember, 2023)
ABSTRACK The idea of ​​scientific development initiated by Thomas Samuel Kuhn is known as the scientific revolution. The idea of ​​a scientific revolution assumes that the development of science takes place in a drastic and revolutionary way. Thomas Samuel Kuhn prefers a view of science that departs from a historical perspective or the history of science as the basis for his thinking. He saw that the history of science should be taught by the philosophy of science to be able to understand the true nature of science and scientific activity. Thomas Samuel Kuhn's thoughts should be associated with Islamic thought so that it becomes a challenge for Muslims in taking the meaning of scientific revolution. The focus of this research is the study of the scientific thought of Thomas Samuel Kuhn, which then draws the thread on the implications of Islamic thought. This study aims to determine knowledge according to the thought of Thomas Samuel Kuhn and its implications when associated with Islamic thought. This research is a literature based research (library research) using descriptive-analytical method. The approach used in this research is a holistic approach that looks at science with its various internal and external aspects.